THE EFFECT OF INDIVIDUAL CHARACTERISTICS AND WORK MOTIVATION ON THE PERFORMANCE OF UPT EMPLOYEES (TESTING QUALITY CERTIFICATION OF FIELD GOODS, DEPARTMENT OF INDUSTRY AND TRADE, NORTH SUMATRA PROVINCE) - Gustria Ningsih; Juliana Nasution (Indonesian Journal of Multidisciplinary Science, 2022)
Human Resources (HR) is an asset to support the success of the goals achieved by an organization or agency. The existence of human resources (HR) is very important in an organization or agency. The existence of competence has a strong effect on employee performance. Competence is the ability to carry out or do a job. In addition, performance is also closely related to the results of one's work. Improved performance individually or in groups will provide competence for the performance of human resources as a whole. Competence is an important part for an employee or employee in carrying out his job well. The Implementing Unit for Quality Certification Examiner of Goods, Department of Industry and Trade, Medan, North Sumatra is a unit or agency in charge of overseeing the technical policy of the metal, machinery, small industry, and domestic and foreign trade industries. The purpose of this study was to examine and analyze the influence of individual characteristics including attitudes, interests, motivation, and compliance with the performance of the employees of the Department of Industry and Trade of the Province of North Sumatra. The research method used was descriptive quantitative with primary data in the form of interviews and observations and secondary data in the form of literature studies. . The results of the study are the influence of characteristics and motivation on employee performance.